2013
DOI: 10.1007/s10695-013-9785-7
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and biochemical effects of microcystin-LR on the Patagonian pejerrey (Odontesthes hatcheri) fed with the toxic cyanobacteria Microcystis aeruginosa

Abstract: We studied accumulation and biochemical effects of microcystin-LR (MCLR) in Odontesthes hatcheri after dietary administration of the cyanobacteria Microcystis aeruginosa (1.3 μg MCLR/g body mass, incorporated in standard fish food). After 12 h, MCLR content in liver did not differ between fish fed with crushed or intact cells, demonstrating O. hatcheri's capacity to digest cyanobacteria and absorb MCLR. In the second experiment, fish received toxic cells, non-toxic cells, or control food; MCLR accumulation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…In the present study, compared with low or high levels of protein, at optimal levels of dietary protein, the contents of ROS, MDA and PC decreased in the gills of grass carp, indicating that an optimal level of dietary protein protected fish from oxidative damage to the gill. To our knowledge, oxidative damage is closely associated with non-enzymatic antioxidants such as GSH and antioxidant enzymes such as CAT and GPx in fish [77,78]. In the present study, compared with low or high levels of protein, at optimal dietary protein levels, the activities of CAT, GPx, GST and GR and the content of GSH were increased in the gills of grass carp, suggesting that at an optimal level of dietary protein the antioxidant capacity of fish gill improved.…”
Section: Optimal Level Of Dietary Protein Attenuated Inflammatory Resmentioning
confidence: 99%
“…In the present study, compared with low or high levels of protein, at optimal levels of dietary protein, the contents of ROS, MDA and PC decreased in the gills of grass carp, indicating that an optimal level of dietary protein protected fish from oxidative damage to the gill. To our knowledge, oxidative damage is closely associated with non-enzymatic antioxidants such as GSH and antioxidant enzymes such as CAT and GPx in fish [77,78]. In the present study, compared with low or high levels of protein, at optimal dietary protein levels, the activities of CAT, GPx, GST and GR and the content of GSH were increased in the gills of grass carp, suggesting that at an optimal level of dietary protein the antioxidant capacity of fish gill improved.…”
Section: Optimal Level Of Dietary Protein Attenuated Inflammatory Resmentioning
confidence: 99%
“…This transport has been studied in mammals, in cell lines, and in fish tissues (Eriksson et al, 1990;Runnegar et al, 1995;Fischer et al, 2005;Boaru et al, 2006;Meier-Abt et al, 2007;Lu et al, 2008). In aquatic animals, laboratory and field studies demonstrate that tissue accumulation of MC is followed by metabolization and elimination, limiting MC accumulation and transfer along the food chain (Williams et al, 1997a, b;Amorim and Vasconcelos, 1999;Soares et al, 2004;Ibelings and Chorus, 2007;Bieczynski et al, 2013). However, the mechanistic events implied in MCLR detoxification and elimination have not been elucidated so far.…”
Section: Have Reported Thatmentioning
confidence: 99%
“…For preparation of everted sacs, pieces of intestine were put in a Petri dish with ice-cold saline and slid onto a crochet needle to expose the mucosal surface. For non-everted sacs, pieces of intestine were cut, placed in (Williams et al, 1997a;Bieczynski et al, 2013), in which ca. 30% of the applied dose has been detected in liver and intestine tissue, respectively.…”
Section: Transport Activity In Intestinal Sacs and Stripsmentioning
confidence: 99%
“…9 Bieczynski et al found that protein-bound MC-LR (L ¼ leucine, R ¼ arginine) represented 66-100% of total MC-LR in the intestine and liver. 10 Our previous studies also revealed that MCs can be strongly adsorbed by sediment, but only be partly recovered by solvent extraction.…”
mentioning
confidence: 90%